2020
DOI: 10.2139/ssrn.3665901
|View full text |Cite
|
Sign up to set email alerts
|

Self-Harming Trade Policy? Protectionism and Production Networks

Abstract: Using monthly data on temporary trade barriers (TTBs), we estimate the dynamic employment e¤ects of protectionism through vertical production linkages. First, exploiting highfrequency data and TTB procedural details, we identify trade policy shocks exogenous to economic fundamentals. We then use input-output tables to construct measures of protectionism a¤ecting downstream producers. Finally, we estimate panel local projections using the identi-…ed trade-policy shocks. Protectionism has small and insigni…cant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Bown et al (2021) find that US anti-dumping (AD) duties against China over the 1998-2016 period cost nearly 2 million jobs in downstream industries. Barattieri and Cacciatore (2020) find that employment in downstream industries falls by 0.5% points following a 1% point increase in the share of imports subject to AD and countervailing (CV) duties in upstream industries. 4 Like us, Barattieri and Cacciatore (2020) also find little evidence that tariffs boosted employment in industries protected by the tariffs.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Bown et al (2021) find that US anti-dumping (AD) duties against China over the 1998-2016 period cost nearly 2 million jobs in downstream industries. Barattieri and Cacciatore (2020) find that employment in downstream industries falls by 0.5% points following a 1% point increase in the share of imports subject to AD and countervailing (CV) duties in upstream industries. 4 Like us, Barattieri and Cacciatore (2020) also find little evidence that tariffs boosted employment in industries protected by the tariffs.…”
Section: Introductionmentioning
confidence: 91%
“…Barattieri and Cacciatore (2020) find that employment in downstream industries falls by 0.5% points following a 1% point increase in the share of imports subject to AD and countervailing (CV) duties in upstream industries. 4 Like us, Barattieri and Cacciatore (2020) also find little evidence that tariffs boosted employment in industries protected by the tariffs. However, neither paper analyzes the effect of safeguard tariffs.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Prusa (1997), Bown and Crowley (2006), Bown and Crowley (2007), Baylis and Perloff (2010), and find that AD tariffs increase imports from non-targeted countries, while Konings et al (2001) and Durling and Prusa (2006) do not find a significant third-country effect. This literature has also found that AD tariffs affect firm performance in the protected sector (Konings and Vandenbussche 2008, Pierce 2011, and Jabbour et al 2019, as well as employment (Trimarchi 2020, Cacciatore 2020, andBown et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Gallaway et al (1999) also evaluates the welfare loss from AD tariffs with a computable general equilibrium model. 8 Flaaen and Pierce (2019) and Trimarchi (2020) find that 2018-19 U.S. tariffs weakly increase employment in the protected sectors, but Barattieri and Cacciatore (2020) and Bown et al (2021) find that anti-dumping tariffs have insignificant employment effect on the protected sectors. Flaaen and Pierce (2019), Barattieri and Cacciatore (2020), and Bown et al (2021) find significant declines in employment in the downstream sectors.…”
Section: Introductionmentioning
confidence: 99%